Mesoporous materials as supports of active molecules: a versatile strategy of functionalization of inorganic oxides - Guntero, Vanina A.; Ferretti, Cristian Alejandro; Mancini, Pedro M. E.; Kneeteman, María N. (My University, 2019)
Ordered mesoporous silica and alumina were functionalized with vanillin, eugenol and their bis-compounds through a microwave assisted process. The physicochemical charac-terization of these materials confirmed the successful immobilization of these molecules onto the surface of these oxides, keeping the ordered mesopore structure of supports and the antioxidant activity of molecules. The results suggest the possibility of applying these materials as a new component of the packaging of aliment or cosmetic with antioxidant properties in the future.
Keywords: mesoporous materials; active molecules; funtionalization